2020
DOI: 10.1026/0932-4089/a000292
|View full text |Cite
|
Sign up to set email alerts
|

Employees First, Technology Second

Abstract: Abstract. Digitization and connectivity are hot topics for nearly every company today; numerous new technologies offer diverse options. In this project, a specific technology − smart glasses − was implemented in a manufacturing company. The implementation process was innovative, as the employees’ perspective was taken into account from the beginning, rather than solely designing the technological aspects and involving the users after decisions were taken. Employees involved with the new technology were surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 24 publications
0
4
0
5
Order By: Relevance
“…Popular change models (e. g., Kotter, 1996;Oreg et al, 2011;Oreg et al, 2018) and the empirical change literature (e. g., Mosadeghrad & Ansarian, 2014;Oakland & Tanner, 2007) agree that one of the most essential activities to ensuring a successful change are employee information and employee participation. Several studies (e. g., Amarantou et al, 2018;Paruzel et al, 2020;Peccei et al, 2011) found that a lack of employee involvement during the change process was associated with a more negative attitude toward change, less change readiness and acceptance of the change, and more resistance to change. Yet, especially for small and mediumsized companies, it is challenging to continuously involve their employees, as they lack expertise in the fields of change management, organizational development, or work design.…”
Section: Project Goalsmentioning
confidence: 99%
“…Popular change models (e. g., Kotter, 1996;Oreg et al, 2011;Oreg et al, 2018) and the empirical change literature (e. g., Mosadeghrad & Ansarian, 2014;Oakland & Tanner, 2007) agree that one of the most essential activities to ensuring a successful change are employee information and employee participation. Several studies (e. g., Amarantou et al, 2018;Paruzel et al, 2020;Peccei et al, 2011) found that a lack of employee involvement during the change process was associated with a more negative attitude toward change, less change readiness and acceptance of the change, and more resistance to change. Yet, especially for small and mediumsized companies, it is challenging to continuously involve their employees, as they lack expertise in the fields of change management, organizational development, or work design.…”
Section: Project Goalsmentioning
confidence: 99%
“…Es bedarf Methoden, konkrete Veränderungen vorauszusehen und abzuschätzen, welche Kompetenzen zukünftig benötigt werden. Denn nur dann können die Beschäftigten entsprechend vorbereitet und qualifiziert werden, um die bevorstehenden Veränderungen erfolgreich zu bewältigen (Paruzel et al 2020). Solche Methoden fehlen bisher; die Prospektive Kompetenzanalyse (ProKA) bietet eine Methode, um diese Anforderungen zu erfüllen.…”
Section: Problemstellung Und Hintergrund Der Instrumentenentwicklungunclassified
“…Wo heute noch Beschäftigte in Handmontage Produkte bauen, werden diese in Kürze vor der Herausforderung stehen, vernetzte Maschinen zu überwachen und mit künstlichen Intelligenzen zusammenzuarbeiten, die reale Prozesse virtuell abbilden (Maier et al 2020;Ren et al 2019). Ob durch den Einsatz digitaler Technologien in der Produktentstehung (Kato-Beiderwieden et al 2020), die Arbeit mit Augmented Reality (AR)-Brillen (Paruzel et al 2020), oder mit akustisch-visuellen Assistenzsystemen (Neumann et al 2020) oder die Digitalisierung des Auftragsdurchlaufs (Schlicher et al im Druck); technologische Neuerungen sind vielfältig.…”
Section: Problemstellung Und Hintergrund Der Instrumentenentwicklungunclassified
See 1 more Smart Citation
“…z. B. Bentler et al 2019;Mlekus et al 2018;Paruzel et al 2020). Gelingt dies nicht, entsteht schnell eine Überforderung mit der Gefahr gesundheitlicher Risiken.…”
unclassified